Management Styles, a vision from conscious and experiential experience (Agroindustria, Sociedad y Ambiente, 2021)
Leadership manifests itself in many ways, some are born, others develop competencies and achieve it with experience and time, however, this ability is part of the managerial style of a person who assumes an active role within an organization and therefore must make decisions and act strategically on a daily basis to meet challenges, lead people, coordinate processes or manage projects of different kinds. This essay offers a look from the experience of a manager more from the praxis than from the conceptualization of the term, which leads to a conscious reflection of how to act and how to face opportunities and threats within organizational contexts. As a starting point, there must be a connection between the definition of management styles and the adoption of leadership not as an option, but as an attitude to face the profile required in modern management.
Keywords: Management; management styles; leadership